An integrated adoption model of cloud computing-based human resource management by SMEs in developing countries: evidence from Bahrain - Milhem, Marwan; Ayyash, Mohannad Moufeed; Ateeq, Ali; Alzaghal, Qadri; Alzoraiki, Mohammed; Almuraqab, Nasser A. Saif; Almeer, Sara (Frontiers in Sustainability, 2025)
Despite the increasing awareness of efficient and technology-driven human resource management at almost all levels of analysis in all organizations, more needs to be done regarding small- and medium-sized enterprises in developing country contexts like Bahrain to explore using cloud computing in HRM. This study applies the Technology, Organization, and Environment framework, extended to include individual managerial innovativeness, in examining the factors influencing the adoption of sustainable cloud computing-based HRM. Data were collected through a cross-sectional survey of 280 upper-level managers and human resource specialists across various SMEs in Bahrain. This data was analyzed using structural equation modeling (SEM) with the help of partial least square (PLS) software. The findings indicate that the technological, organizational, and environmental contexts greatly impact the adoption of sustainable cloud computing-based HRM, while individual managerial innovativeness does not. This study has significant implications for any human resource department looking to shift its operation onto a sustainable cloud computing platform in a developing country.